URGENSI HUKUM ADAT DALAM PEMBAHARUAN HUKUM PIDANA NASIONAL - Rahmat Hi. Abdullah (Universitas Lampung, 2015)
Recognition of the existence of legal values and sense of justice that life is constitutionally recognized as the author explained earlier. One of the key concepts that evolved form of legal recognition or live in the community is the adoption of the system of sanctions in customary law (customary criminal) in the national legal system. Recognition and protection of sanction customary law becomes an important thing in the life of indigenous peoples, for the customary sanctions, then it can be constructed or create a balance and social harmony, interests between the human race and the individual, between the alliance (group) and wider society that is the basis from the minds of traditional Indonesian nation. Recognition of the importance of values in society as customary law (customary criminal) in the renewal of the national criminal law as the national law reform agenda is a necessity and demand to the fulfillment of social justice in accordance ideals of the Indonesian nation.Keywords: Customary, Existence, Criminal Law Reform